Quantifier Particles and Compositionality - Szabolcsi, Anna (Proceedings of the Amsterdam Colloquium, 2013)
In many languages, the same particles build quantifier words and serve as connectives, additive and scalar particles, question markers, existential verbs, and so on. Do the roles of each particle form a natural class with a stable semantics? Are the particles aided by additional elements, overt or covert, in fulfilling their varied roles? I propose a uni ed analysis, according to which the particles impose partial ordering requirements (glb and lub) on the interpretations of their hosts and the immediate larger contexts, but do not embody algebraic operations themselves.